Transformasi Digital Pada Sistem Isu Manajemen Pada Bidang Akuntansi: Studi Perkara Dan Seni Manajemen Implementasi - Sentiyani Sentiyani; Rayyan firdaus (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Digital transformation has become an inevitability in various sectors, including accounting. This article explores how digital transformation is affecting management information systems (MIS) in the accounting field. Case studies of several companies that successfully implemented digital technology in their accounting practices in 2020 are explained to provide practical insights. Additionally, effective implementation strategies to facilitate these changes are reviewed. The study results show that digital transformation can increase efficiency, accuracy and transparency, but also requires a good strategic approach to overcome challenges that may arise.